Multi-criteria decision making of biomass gasification-based cogeneration systems with heat storage and solid dehumidification of desiccant coated heat exchangers. (15th October 2021) - Li, Xian; Chen, Jialing; Sun, Xiangyu; Zhao, Yao; Chong, Clive; Dai, Yanjun; Wang, Chi-Hwa
Abstract: Biomass gasification-based cogeneration systems integrated with dehumidification of desiccant coated heat exchangers, covering the cogeneration system inclusive of sensible heat storage and internal heat recovery (SC-1), the cogeneration system inclusive of sensible heat storage (SC-2), and the cogeneration system exclusive of heat storage and internal heat recovery (SC-3), are introduced and comparatively investigated on the energetic and economic performances. The developed models of the cogeneration systems are embedded into a multi-criteria decision-making framework to find the optimal system configuration and parameters. The most favorable scheme (SC-1) – that reaches an overall energy efficiency of 0.963, net present value of 1, 429, 400 USD, levelized total cost of 646, 835 USD/year, payback period of 3.7, heat storage tank of 7 m 3, heat recovery tank of 2.1 m 3, jacket heat rate of 290 kW, and nominal electric power of 629 kWe – is determined. The sensitivity analysis indicates that the net present value is most sensitive to the electricity tariffs, followed by the biomass feedstock price and the selling price of electricity to utility grid. The overall energy efficiency of 0.81–0.995, the net present value of −470, 400–6, 166, 900 USD, and the payback period of 1.5–13.1 were achieved against the price variation range of ±80%. Graphical abstract: Image 1 Highlights: Biomass gasification-based cogeneration systems were introduced. The proposed cogeneration system was coupled with solid desiccant dehumidification. A decision-making framework was developed to find the optimal system scheme. The system scheme with both heat storage and heat recovery is most favorable. Sensitivity analysis associated with the optimal schemes were conducted.